Acceleration of a high-current proton beam in a linear induction accelerator at its compensation by electron beams - Fedorovskaya, O.V.; Maslov, V.I.; Onishchenko, I.N. (Вопросы атомной науки и техники, 2022)
The dynamics of a high-current proton beam in the cusp magnetic field and in the uniform magnetic field of the drift region in the presence of an accelerating field in the cusp region and of two types of compensating electron beams (before and after the cusp) has been studied. It is shown that for the taken beam parameters and magnetic field it is impossible to accelerate a proton beam of the density higher than 10¹² cm⁻³ with maintaining its initial transverse size and monoenergeticity. Вивчено динаміку сильнострумового протонного пучка в магнітному полі каспа та в однорідному магнітному полі дрейфової області за наявності в області каспа прискорюючого поля та двох типів електронних пучків (до і після каспа). Для вибраних параметрів пучків та магнітного поля показана неможливість прискорити протонний пучок щільністю понад 10¹² см⁻³ зі збереженням його поперечних розмірів та моноенергетичності. Изучена динамика сильноточного протонного пучка в магнитном поле каспа и в однородном магнитном поле дрейфовой области при наличии в области каспа ускоряющего поля и двух типов компенсирующих электронных пучков (до и после каспа). Для выбранных параметров пучков и магнитного поля показана невозможность ускорить протонный пучок плотностью большей 10¹² см⁻³ с сохранением его поперечных размеров и моноэнергетичности.